Rho-omega mixing and neutron-proton self-energies in the Walecka model - Krein, G. [UNESP]; Menezes, D. P.; Nielsen, M. (Elsevier, 1992)
We use the Walecka model to investigate the influence of the charge symmetry breaking ρ0-ω mixing interaction on the neutron-proton self-energy difference in nuclear matter. Using 2mρ〈ρ0|H|ω〉 = -4500 MeV2, and employing the Dirac-Hartree-Fock approximation, we find that the neutron-proton self-energy difference is a decreasing function of the nuclear matter density, and that it has a value of the order of 700 keV at the normal density. The results indicate that the Nolen-Schiffer anomaly might be explained by means of relativistic nuclear models in a similar way as it is explained by means of non-relativistic models.